Eye Shape Illusions Induced by Eyebrow Positions. (May 2015) - Matsushita, Soyogu; Morikawa, Kazunori; Mitsuzane, Saya; Yamanami, Haruna
We investigated whether the position of the eyebrows influences the perceived shape of the eyes by employing psychophysical measurements. Experiment 1 used arched and straight eyebrows at five different inclinations as stimuli and measured the perceived inclination of the eyes. The results demonstrated that the eyes are perceived to be somewhat inclined in the same direction as the eyebrows. Experiment 2 measured the perceived eye size by manipulating the distance between the eyes and the eyebrows and the curvature of the eyebrows across three levels. The results showed that the lower eyebrows (ie closer to eyes) made the eyes appear larger and the higher eyebrows made the eyes appear smaller, while eyebrow curvature had no effect on perceived eye size. Experiment 3 examined the role of the eye–eyebrow distance in the eye inclination illusion shown in experiment 1. The eye inclination illusion was unaffected by the eye–eyebrow distance, suggesting that the eye inclination illusion and the eye size illusion may involve different kinds of assimilation. These illusions are discussed in terms of face perception and possible practical applications.